Design And Implementation Of Attendance Marking Camera - et. al., Dr. NayanaDK, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Attendance system by utilizing camera as a source to capture image is made as a intriguing, challenging and accurately for real time system. It is not easy to mark the attendance for students in a large classroom. However, the attendance system using image recognition have issues that allows the research for improving the present research for making the attendance system to work well. This paper also provides information and suggestion for future work.